Hubungan Antara Pengetahuan Ibu Tentang Pola Pemberian Makanan Dengan Status Gizi Balita Usia 7 – 24 Bulan Di PMB Hj. Anna Haifani, SST,SKM,M.Kes Karang Tengah Tangerang Tahun 2022 - Pratiwi Cahya Wardhani; Siti Nurbaiti; Sofiah KS (NHM PRESS, 2023)
WHO states that malnutrition is still a problem in the world, in Indonesia malnutrition is experienced by many children under five. According to Riskesdas (2018) that underfives in Indonesia are undernourished at 17.7%, which is still below the target of the RJPMN, which is 17%. The lack of consumption of food and the quality of nutrition provided by the family affects the nutritional status of children under five and there are factors including the mother's education level, mother's age, mother's knowledge and mother's occupation. The purpose of this study was to determine the relationship between mothers' knowledge about feeding patterns and the nutritional status of children aged 7-24 months at PMB Hj.Anna Haifani,SST,SKM.M.Kes Karang Tengah Tangerang. After being tested statistically with the Chi-Square test, the mother's knowledge was obtained with the result P-value 0.042 > α 7.857 and the mother's age P-value 0.026 > α 7.857. There are several factors that can affect the mother's knowledge about feeding patterns with the nutritional status of children aged 7-24 months, but mother's knowledge and mother's age are the main factors.